Bacterial biofilm within diseased pancreatic and biliary tracts. Issue 3 (11th February 2005) - Swidsinski, A; Schlien, P; Pernthaler, A; Gottschalk, U; Bärlehner, E; Decker, G; Swidsinski, S; Strassburg, J; Loening-Baucke, V; Hoffmann, U; Seehofer, D; Hale, L P; et al.
Abstract : Background: Bacterial community structures in human pancreatic and biliary tracts were evaluated. Methods: Gall bladder stones from 153 patients, 20 gall bladder walls, six common duct stones, 52 biliary stents, 21 duodenal biopsies, nine pancreatic duct biopsies, and five bile ducts were investigated using fluorescence in situ hybridisation (FISH) with ribosomal RNA targeted Cy3/Cy5 (carbocyanine) labelled oligonucleotide probes. Result: Duodenal, gall bladder, and bile duct walls were free of bacteria. A dense multispecies bacterial biofilm was present within the pancreatic duct of patients with calcific pancreatitis and within biliary stents, irrespective of diagnosis. The concentration, density, and amenability of the biofilm to FISH and DNA staining declined progressively with the grade of stent occlusion. The lowest detectable bacterial concentrations were found by FISH in completely occluded stents and brown/mixed gall stones. Bacteria were not detectable with FISH in cholesterol gall stones. Conclusions: A wide range of different branches and groups of bacteria participate in the development of biofilms on the surfaces of foreign bodies, such as biliary stents, mixed gall stones, or calcific pancreatic ducts, but not on the surface of pure cholesterol gall stones. Occlusion of stents leads to progressive extinction of the biofilm and mummification of its components. Deposition of cholesterol or other substances within the biofilm matrix may be a novel mechanism of host defence against bacteria present in these biofilms.